Diseño de un Protocolo de Pruebas del Sistema Airbag mediante la Interpretación de Oscilogramas de Operación - Jeréz Mayorga, Daniela Alexandra (2017)
In the study ofthe system AIRBAG of a vehicle of tourism 1600cc; they focused and analyzed his graphs depending on the elements of the system[1], there took information of the speed sensors, sensors of impact, module of control, wired up of the system, spiral contactor, socket of connections; in addition the present project used equipments of measurement and diagnosis, multimeter self-propellingly, scanner, and oscilloscope. The connections were created between the instruments of measurement and of diagnosis adapting the vehicle for experimental tests and hereby to obtain informationof the elements of the system.There took specific information of every element using flow grasses of operation, the information was: electrical signs of normal operation, codes of faults ofthe system; and by means of an oscilloscope there were obtained oscillograms of operation of every element, this information was interpreted and compared with waited by the manufacturer to develop pictures of diversion, PIDs and the proposed solutions.The information obtained in normal conditions of operation and of fault was based on oscillograms of operation, once evaluated this information, there were designed the protocols of tests that allowed us to realize a work of maintenance and control of more efficient functioning.